2008
DOI: 10.1371/journal.ppat.1000021
|View full text |Cite|
|
Sign up to set email alerts
|

RNA Interference Screen Identifies Abl Kinase and PDGFR Signaling in Chlamydia trachomatis Entry

Abstract: To elucidate the mechanisms involved in early events in Chlamydia trachomatis infection, we conducted a large scale unbiased RNA interference screen in Drosophila melanogaster S2 cells. This allowed identification of candidate host factors in a simple non-redundant, genetically tractable system. From a library of 7,216 double stranded RNAs (dsRNA), we identified ∼226 host genes, including two tyrosine kinases, Abelson (Abl) kinase and PDGF- and VEGF-receptor related (Pvr), a homolog of the Platelet-derived gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
205
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(211 citation statements)
references
References 88 publications
5
205
1
Order By: Relevance
“…S5; Hantschel et al, 2003;Nagar et al, 2003). It has previously been reported that infection of ABL/ARG / knockout mouse fibroblasts leads to a 50% reduction of Tarp phosphorylation, which suggests that ABL could be the initial Tarp kinase (Elwell et al, 2008). Interestingly, phosphorylation of the H. pylori protein CagA and the EPEC effector Tir was also shown to involve ABL (Swimm et al, 2004;Poppe et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…S5; Hantschel et al, 2003;Nagar et al, 2003). It has previously been reported that infection of ABL/ARG / knockout mouse fibroblasts leads to a 50% reduction of Tarp phosphorylation, which suggests that ABL could be the initial Tarp kinase (Elwell et al, 2008). Interestingly, phosphorylation of the H. pylori protein CagA and the EPEC effector Tir was also shown to involve ABL (Swimm et al, 2004;Poppe et al, 2007).…”
Section: Discussionmentioning
confidence: 87%
“…The ABL kinases can be activated through interaction of their SH2 domains with cellular substrates (Lewis and Schwartz, 1998;Barilá et al, 2000). ABL1 and ABL2 have been shown to be among the human kinases that phosphorylate Tarp (Elwell et al, 2008; two (VAV2 and PI3K) that had previously been identified. Highaffinity interactions with two proteins, the serovariant L2-specific protein NCK2 and the serovariant D and L2 common interaction partner SHC1, were experimentally validated, and the interaction of Tarp with SHC1 was studied in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell surfaceexposed protein disulfide isomerase (PDI) has also been shown to play an important role in EB attachment and entry (Abromaitis and Stephens 2009). Recent studies have revealed an unexpected role for growth factors and their receptors in Chlamydia binding (Elwell et al 2008;Kim et al 2011). A genome-wide loss-of-function RNAi screen in Drosophila S2 cells identified a potential role for the platelet-derived growth factor receptor (PDGFR), a transmembrane tyrosine kinase, in Chlamydia binding.…”
Section: Mechanisms Of Chlamydia Invasion Of Epithelial Cellsmentioning
confidence: 99%
“…Whereas the human pathogen C. trichomatis can initiate infection in S2 cells, it cannot complete its lifecycle [48]. A focused screen for early events in the lifecycle included actin regulators and led to the identification of 28 factors including the Abl kinase and components of the PDGFR signaling pathway as essential for early steps in the C. trichomatis infection both in insect and mammalian cells [49]. C. caviae, a guinea pig pathogen, productively infects S2 cells and was used to screen a genome-wide library, leading to the identification 31 genes that are specifically required for C. caviae replication [39].…”
Section: Bacterial Survival and Growthmentioning
confidence: 99%